A case of bilateral breast gangrene in lactating non diabetic young lady - Mahran, Khaled; Heeny, Amr El- (Indian Journal of Case Reports, 2016)
This report describes an unusual case of gangrene affecting the breast in a lactating non-diabetic patient.She was admitted to Minia University hospital complaining of swelling, pain and blackish discoloration of both breasts that was more extensive on the left side. Wound cultures revealed heavy growth of styphalcoccusaureus showing sensitivity to linzeolid, Methicillin and Vancomycin.Blood culture was sterile. Examination revealed that both breasts were large, tender and the gangrene involved all quadrants of the left breast and the medial side of the right breast (15x7 cm). Debridement was carried out and then skin graft was carried out for the left breast and primary closure for the right breast. The objective of this case report is to study clinical presentation and management of youngfemale with breast gangrene.